COGNITIVE ARITHMETIC: Mental Processing of Addition and Multiplication - - Sugiyanto (Faculty of Psychology Universitas Gadjah Mada, 1994)
In contrast to the many studies of languages processing, there have been relatively few studies of arithmetic processing in cognitive psychology. Author of textbooks for university students, such as Solso (1991), do not appear to feel a need to address cognitive arithmetic issues in their books.